The COVID-19 pandemic and war. Issue 1 (February 2022) - Gugushvili, Alexi; Mckee, Martin
Could there be a symbiotic relationship between COVID-19 and conflict? On the one hand, circumstances associated with armed conflicts may give rise to greater spread of the virus, while, on the other hand, the COVID-19 pandemic may create conditions for violence through heightened xenophobia and nationalism or may change the dynamics of existing conflicts. We illustrate this with the example of war in the South Caucasus, one of the hot spots of the pandemic. Elsewhere, COVID-19 may have reduced the intensity of conflicts in some places, but it also may have contributed to anti-government protests and communal violence. We call for greater emphasis on traditional public health measures in unstable settings coupled with actions to hasten the peaceful resolution of ongoing conflicts.